Sistem Penerapan Metode Pencatatan Dan Penilaian Persediaan Barang Dagang Di Togamas - Ni Made Rianita (ARTHA SATYA DHARMA, 2021)
The purpose of this study was to determine how the system of applying the method of recording and valuing merchandise inventory in TOGAMAS Toko Buku Diskon Singaraja. This research was a quantitative research. The data collection technique used was documentation. Data analysis techniques used in this study were two methods, namely the inventory assessment method consisting of the FIFO method, the LIFO method, and the Average method. The recording method was also divided into two, namely the Periodic Inventory System and the Perpetual Inventory System. All that had been examined in this study showed significant results related. For this reason, it is expected that Togamas Toko Buku Diskon Singaraja should always apply the system of recording and valuing merchandise inventory that has been carried out so far.